1992
DOI: 10.1177/019262339202000313
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Quinolone Arthropathy—Acute Toxicity to Immature Articular Cartilage

Abstract: A class effect of quinolone antibacterial agents observed during animal toxicity testing is a specific arthropathy (QAP). Despite the growing list of laboratory animals susceptible to QAP and reports of arthralgia in patients treated with quinolones, the potential for QAP development in humans remains unknown. This review discusses current concepts in the biology of articular cartilage and how these concepts elucidate QAP pathogenesis. Biomechanical forces within synovial joints and toxicokinetic properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
77
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 80 publications
7
77
0
Order By: Relevance
“…3). These macro-and micropathological findings were in agreement with previous results of known quinolones in immature dogs [1,3,7,11], and basically resembled those reported in multiple species such as rats [4], rabbits [2], non-human primates [9] and others [5,6], although there were slight differences in the arthropathic dose among the quinolones. Unfortunately, the sensitivity of MR imaging for the detection of vesicular lesions in articular cartilage remains an unresolved issue, as Gough et al [2] reported.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…3). These macro-and micropathological findings were in agreement with previous results of known quinolones in immature dogs [1,3,7,11], and basically resembled those reported in multiple species such as rats [4], rabbits [2], non-human primates [9] and others [5,6], although there were slight differences in the arthropathic dose among the quinolones. Unfortunately, the sensitivity of MR imaging for the detection of vesicular lesions in articular cartilage remains an unresolved issue, as Gough et al [2] reported.…”
supporting
confidence: 91%
“…At necropsy, all dogs given ofloxacin exhibited multifocal fluid-filled vesicles (2 × 2 mm to 5 × 12 mm, round-and oval-shaped blisters) with partial erosion between the patellar surface and medial condyles of the distal head of the femurs (Fig. 2), and elicited an increased amount of Arthropathy in immature animals brought about by new quinolone antibacterial agents (quinolones) is an unusual adverse reaction observed with all known quinolones [1][2][3][4][5][6]10]. In particular, immature dogs among the experimental animals tested have shown the most susceptibility to cartilage lesions in the epiphyses constituting almost all diarthrodial joints [3,10].…”
mentioning
confidence: 99%
“…In vitro studies with human lymphocytes exposed to enrofloxacin (ENR) and ciprofloxacin revealed an increase in the chromosomal aberrations, detected as chromatid and chromosome breaks and gaps (Gorla et al, 1999). FQs have been reported to cause neonatal alterations in articulation cartilages, bone growth and tendons, both in humans and animals (Patterson, 1991;Gough et al, 1992;Hildebrand et al, 1993;Forster et al, 1996;Simonin et al, 1999;Stahlmann, 2003;Lemus et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, quinolones have been reported to induce arthropathy in juvenile animals such as mice [12], rats [4, 9, 10], rabbits [11], dogs [3, 5, 8, 20], nonhuman primates [17] and others [1, 2] as a class effect of these derivatives. Among these species, the juvenile dog is thought to be most susceptible to articular cartilage lesions [6,19,20].In our previous report [23], the arthropathic lesion due to ofloxacin was observed only in juvenile dogs, despite the fact that the drug concentration in the synovial fluid and articular cartilage of immature dogs (3-month-old) was equal to or lower than those in mature dogs (18-month-old). Kato and coworkers [10] have indicated that metabolically active immature chondrocytes are more sensitive to the effects of a quinolone, compared with inactive mature cells in the ex vivo study using 3 H-thymidine.…”
mentioning
confidence: 87%
“…However, quinolones have been reported to induce arthropathy in juvenile animals such as mice [12], rats [4,9,10], rabbits [11], dogs [3,5,8,20], nonhuman primates [17] and others [1,2] as a class effect of these derivatives. Among these species, the juvenile dog is thought to be most susceptible to articular cartilage lesions [6,19,20].…”
mentioning
confidence: 99%